Оцінювання невизначеності відтворення одиниці об’ємної витрати газу із застосуванням удосконаленої поршневої установки - Кепещук, Д. Т. (ХНУРЕ, 2021)
The metrological analysis of the developed reference piston installation of the improved design for reproduction and measurement of a gas expense is carried out. Factors influencing the accuracy of reproduction and transmission of the volume and volume flow of gas are analyzed. Based on experimental data, the values of the components of the total uncertainty, which are associated with design deviations of the cylinder dimensions and additional effects of changes in temperature and pressure of the internal environment, are calculated. The expediency of improving the design of the reference piston installation is substantiated, as the expanded uncertainty reduced to the control reproducible volume was 0.025%.